Nueva definición de “vida”: La “vida” es una reacción en cadena que acumula anti-entropía - Arbaiza Escalante, Luis Bertrand (2019)
We lack of a satisfactory definition of "life", for which one is proposed based on one hipótesis: "Life" is a chain reaction that accumulates anti-entropy. From this axiom the following consequences can be inferred: Life is characterized as a physical phenomenon; There are no counter-examples or intermediate individuals; The accumulated anti-entropy is material causality whose effect prolongs the chain reaction; There can be life without cells; Viruses are life, prions are not; Terrestrial life began with the first RNA; The process of accumulation of anti-entropy is abiotic, evolution is particular case of this; Recognizing extraterrestrial life does not imply the analysis of individuals but their relationships: Life can exist in other conformations of matter and the exclusively asexual reproduction species are not life.